2009
DOI: 10.1055/s-0029-1202259
|View full text |Cite
|
Sign up to set email alerts
|

Association ofGNB3C825T Polymorphism with Peak Oxygen Consumption

Abstract: The C825T single nucleotide polymorphism (SNP) in the guanine nucleotide-binding protein, beta polypeptide 3 ( GNB3) gene gives rise to a splice variant, GNB3s that has enhanced G protein activation and signal transduction activity. This variant has been reported to be associated with cardiovascular disease, diabetes and obesity. We studied this SNP in 95 healthy 18 to 30 year-old African American university students to determine its association with aerobic capacity and cardiorespiratory fitness as measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Rankinen et al (2002b) found that the GNB3 C825T polymorphism plays a minor role in heart rate and body fatness regulation in African Americans, as well as in the responsiveness of resting blood pressure to endurance training in African American women. This polymorphism was also associated with VO 2max in non‐athletes (Faruque et al, 2009), and our group recently reported a higher frequency of the TT genotype in Israeli elite endurance athletes than in sprinters of the same origin (Eynon et al, 2009).…”
mentioning
confidence: 69%
“…Rankinen et al (2002b) found that the GNB3 C825T polymorphism plays a minor role in heart rate and body fatness regulation in African Americans, as well as in the responsiveness of resting blood pressure to endurance training in African American women. This polymorphism was also associated with VO 2max in non‐athletes (Faruque et al, 2009), and our group recently reported a higher frequency of the TT genotype in Israeli elite endurance athletes than in sprinters of the same origin (Eynon et al, 2009).…”
mentioning
confidence: 69%
“…Black subjects with the GNB3 TT genotype had a greater heart rate response to the cold pressor test of sympathetic activation (28), suggesting the GNB3 polymorphism may influence vascular tone through alterations of autonomic function. Metabolic stress testing revealed an association between the GNB3 T allele and poorer peak oxygen consumption and altered heart rate variability, further suggesting that the T allele may be associated with autonomic modulation and cardiovascular stress response (29). …”
Section: Discussionmentioning
confidence: 99%
“…It is associated with VO 2max in nonathletes [5] , and Eynon et al recently reported a higher frequency of the TT genotype in Israeli elite endurance athletes than in sprinters of the same origin [4] . Whether the latter results can be extrapolated to other populations remains to be elucidated.…”
Section: Gnb3 C825t Polymorphism and Elite Athletic Status: A Replicamentioning
confidence: 98%